Quercetin inhibits steroid-induced hypergluconeogenesis in Saccharomyces cerevisiae - Victor Arokia Doss; Gowtham Subramaniam; Keerthana Manoharan (Future Journal of Pharmaceutical Sciences, 2025)
Abstract Background Steroid-induced hypergluconeogenesis is a significant contributor to hyperglycemia, often complicating the therapeutic use of steroids. This study investigates the potential of quercetin, a naturally occurring flavonoid, to mitigate steroid-induced hypergluconeogenesis in Saccharomyces cerevisiae. The levels of glucose, total proteins, free amino acids, pyruvate, lactate and antioxidants were assessed in the quercetin-treated yeast cells induced with betamethasone at different time intervals. The glucose uptake potential of yeast cells treated with quercetin was also studied and also the effect of steroids and quercetin on cell viability was analyzed. Results Our results show that quercetin effectively reduces gluconeogenesis by normalizing the levels of metabolites involved in the process and alleviates the hyperglycemic effects associated with steroid exposure. Quercetin-treated yeast cells also demonstrated a better uptake of glucose. Additionally, quercetin was found to improve the overall cell viability highlighting its role in modulating glucose metabolism. Conclusion These outcomes suggest that quercetin can serve as a promising adjunct therapy for managing steroid-induced metabolic disturbances, providing a natural and effective approach to counteracting steroid-induced hyperglycemia.